If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(3-3)=27
We move all terms to the left:
3x(3-3)-(27)=0
We add all the numbers together, and all the variables
3x0-27=0
We add all the numbers together, and all the variables
3x-27=0
We move all terms containing x to the left, all other terms to the right
3x=27
x=27/3
x=9
| 21=x-(-5) | | 11+(7x+4)=57 | | 11b^2=-11b-12 | | −3x+1=9+5x | | m/3=-1.5 | | 8896=x/64 | | 49=4j+17 | | 8896=x÷64 | | 90=6(p+3) | | 24+3s=72 | | 6h+4=28 | | 2(s+22)=80 | | 2(z+5)=3(4z+2)−1 | | 2s+22=80 | | 8.42−5.1h=–6.9h−6.88 | | 7+2p=-9+3p+6 | | 2d-3(d+5)=0 | | 2d+1/2=3/5 | | 5*2b-17=25-11*2 | | 7+2p=-9=3p+6 | | 15+9d=69 | | 2g+g+4g=8^2-6^2 | | 2(2x+1)+3=10 | | 4+5u=11 | | 2l+l=5 | | 2k-5=21 | | -4+5n=-9 | | 4(x+1)+2=4+2x | | 10r-4=6 | | -9+w=-18- | | 10+3i=13 | | 5(-3x-3)=2(3x-7) |